2019
DOI: 10.1038/s41396-019-0367-2
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota is largely independent of host genetics in regulating fat deposition in chickens

Abstract: The gut microbiota has an important role in animal health and performance, but its contribution is difficult to determine, in particular given the effects of host genetic factors. Here, whole-genome sequencing of the hosts and 16S rRNA gene sequencing of the microbiota were performed to separate the effects between host genetics and the microbiota in the duodenum, jejunum, ileum, caecum and faeces on fat deposition in 206 yellow broilers reared under identical conditions. Despite the notable spatial variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
192
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(212 citation statements)
references
References 91 publications
19
192
1
Order By: Relevance
“…Members of the chicken caecal microbiota have also been implicated in the recycling of nitrogen by the degradation of nitrogenous compounds [11] and the synthesis of amino acids [12]. One study demonstrated that 21% of the variation in chicken abdominal fat mass could be attributed to the caecal microbiota composition, when controlling for host genetic effects [13]. Differences have also been observed between birds with high and low feed efficiency [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the chicken caecal microbiota have also been implicated in the recycling of nitrogen by the degradation of nitrogenous compounds [11] and the synthesis of amino acids [12]. One study demonstrated that 21% of the variation in chicken abdominal fat mass could be attributed to the caecal microbiota composition, when controlling for host genetic effects [13]. Differences have also been observed between birds with high and low feed efficiency [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Later, with the development of next-generation sequencing and larger sample sizes of twin studies, the role of host genetics in the gut microbiota structure was confirmed, followed by detection of associations between host SNPs and bacterial abundance [9,14,16]. However, the level of strength of host genetic impact on the gut microbiota has not reached consensus yet, primarily due to the different populations used in the studies, with variations in genetic distance, as well as other factors such as age, diet, and living style [17,18,[50][51][52]. These factors might have masked the significance of the host genetic role in the gut microbiota in previous studies, leading to a failure in the identification of repeatable associations between host SNPs and bacterial abundance.…”
Section: Discussionmentioning
confidence: 96%
“…With recent advanced technology, specifically genome-wide association study (GWAS), multiple associations have been identified between single nucleotide polymorphisms (SNPs) genotypes, primarily located in genes associated with host metabolic syndrome and immune disease, and abundance of commensal bacteria [14][15][16]. However, recently the statistical significance of associations between host SNPs and individual bacterial taxa has been challenged [17], and additional studies report that environmental factors dominate host genetics in shaping the gut microbiota [18,19]. The discrepancies in interpreting the role of host genetics and environmental factors might be due to population variation, genetic distance, age, and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have implicated it as playing a role in nutrition, including in the production of SCFAs and the recycling of nitrogen from uric acid (10, 11, 76). Differences have also been observed in the cecal microbiota communities between chickens with differing feed efficiencies and abdominal fat accumulation (13–15). It may therefore be possible to increase chicken productivity by the manipulation of the chicken cecal microbiota.…”
Section: Discussionmentioning
confidence: 99%